Advancing critical thinking through SDGs 7-oriented interactive STEM media in elementary education - Melinda Mu'aadzah; Jajang Bayu Kelana; Faridillah Fahmi Nurfurqon (Jurnal Profesi Pendidikan, 2026)
Elementary school students' critical thinking skills remain low due to a lack of active engagement and minimal use of interactive learning media and instructional models, resulting in difficulties in comprehending subject matter, analyzing problems, and drawing logical conclusions. This study aims to develop SDGs 7-based interactive media integrated with STEM learning to improve students' critical thinking skills. The interactive media contextually addresses the issue of clean and affordable energy sustainability in alignment with real-world problems. This study employed a Research and Development (R&D) method using the ADDIE model. Implementation followed a one-group pretest-posttest design conducted in two stages: a limited trial involving 34 Grade V-B students and a broad trial involving 67 Grade V-A and V-C students at SDN Utama Mandiri 1, Cimahi City. Data collection techniques included interviews, media expert and content expert validation sheets, pretest-posttest instruments, and student response questionnaires. Validation results indicated that the media was rated as highly feasible, with scores of 95% from the media expert and 82% from the content expert. The paired sample t-test revealed a significant difference between pretest and posttest scores in both the limited and broad trials (p = 0.000 < 0.05). Furthermore, N-Gain analysis showed a moderate improvement in critical thinking skills, with a score of 0.42 in the limited trial and 0.63 in the broad trial. Student responses toward the media were categorized as excellent. These findings suggest that the SDGs 7-based interactive media developed is feasible for use and has the potential to support the improvement of elementary school students' critical thinking skills.